Ecotourism cooperative management for resources protection of Taman Negara National Park, Malaysia - Mohd, Abdullah; Yip, Hin Wai; Yaman , Amat Ramsa (Forestry Department Peninsular Malaysia, 2008)
Ecotourism in protected areas in combination with local community participation by providing services and protecting the bio diversities connote sustainable use of such resources. In spite of this, issues have cropped up in protected areas on safeguarding the resources integrity which the industry highly rely on. This conservation initiative can be pursued effectively through a participatory management approach between direct stakeholders or players such as in Taman Negara national park administration and local ecotourism operators. A study was conducted based on the conception of co-operative management approach upon the detrimental impacts caused by increasing visitations and recreational activities especially in remote areas of the park and illegal activities done by the locals. A survey was conducted on the management staff and local operators to elicit their responses on the related issues. Statistical analysis such as descriptive and factor analysis were used to determine the main factors that contributed to co-management between the stakeholders. The four factors identified include joint field operation, capacity building, best practices, and intellectual forum among the players. This co-management process could be incremental as involvement among the participants increases in due time. This management technique could be useful in order to make the local communities be more involved in sustainable management of the resources. In addition, this institutional arrangement between the parties will guide the administration to consider the locals in the management partnership.